Catalytic properties, localization, and in vivo role of Px IV, a novel tryparedoxin peroxidase of Trypanosoma brucei - Liu, Ilon; Bogacz, Marta; Schaffroth, Corinna; Dirdjaja, Natalie; Krauth-Siegel, Renate (Molecular and biochemical parasitology, 2016)
Px IV is a distant relative of the known glutathione peroxidase-type enzymes of African trypanosomes. Immunofluorescence microscopy of bloodstream cells expressing C-terminally Myc6-tagged Px IV revealed a mitochondrial localization. Recombinant Px IV possesses very low activity as glutathione peroxidase but catalyzes the trypanothione/tryparedoxin-dependent reduction of hydrogen peroxide and, even more efficiently, of arachidonic acid hydroperoxide. Neither overexpression in bloodstream cells nor the deletion of both alleles in bloodstream or procyclic parasites affected the in vitro proliferation. Trypanosoma brucei Px IV shares 58% of all residues with TcGPXII. The orthologous enzymes have in common their substrate preference for fatty acid hydroperoxides. However, the T. cruzi protein has been reported to be localized in the endoplasmic reticulum and to be specific for glutathione as reducing agent. Taken together, our data show that Px IV is a low abundant tryparedoxin peroxidase of T. brucei that is not essential, at least under culture conditions.
Gesehen am 27.05.2020